Pelvic ultrasound and pubertal attainment in girls with sexual precocity: the pivotal role of uterine volume in predicting the timing of menarche - Cattoni, Alessandro; Russo, Gianni; Capitoli, Giulia; Rodari, Giulia; Nicolosi, Maria Laura; Molinari, Silvia; Tondelli, Daniele; Pelliccia, Ciretta; Radaelli, Silvia; Arosio, Andrea Mario Luciano; Fontana, Katia; Tattesi, Giulia; et al. (Frontiers in Endocrinology, 2024)
Introduction. Among girls assessed for pubertal precocity, pelvic ultrasound (pUS) may represent a pivotal tool to predict the time expected to elapse between sonographic assessment and the onset of menarche (T US-M ). Accordingly, the present analysis is meant to define the statistical relationship between sonographic parameters and T US-M , in order to identify the most reliable predictor of the timing of menarche. Methods. Retrospective, multicenter analysis. Girls assessed for sexual precocity and showing sonographic and clinical findings consistent with pubertal onset upon referral were considered eligible. Patients treated with GnRH analogues were excluded and only those who had subsequently achieved complete and spontaneous pubertal attainment and for whom the exact date of menarche was available were included. Overall, we enrolled 184 girls from five tertiary care Italian Centers. Results. The time elapsed (months) between baseline endocrine assessment and spontaneous achievement of menarche showed a negative statistically significant correlation (p<0.0001) with LH (r:-0.61), FSH (r:-0.59), estradiol (r:-0.52) and stimulated LH values (r:-0.58). Among pUS parameters, ovarian volume (r:-0.17 left, -0.30 right) and uterine body-to-cervix ratio (r:-0.18) poorly correlated with T US-M , while uterine diameters (r:-0.61 longitudinal, -0.64 anteroposterior) and volume (r:-0.70) achieved a highly statistical significance (p<0.0001). Uterine volume (UV) showed a negative logarithmic relationship with T US-M and represented the most reliable predictor of the timing of menarche in uni-and multivariable analyses (p <0.001). ROC analyses identified the UV thresholds that best predict the onset of menarche within 18, 12 and 6 months, respectively: 3.76, 6.02 and 8.80 ml. Conclusions. The logarithm of UV shows the best statistical performance in predicting the timing of menarche in girls assessed for pubertal precocity. Accordingly, we developed a user-friendly online application that provides clinicians with an estimation of the months expected to elapse before menarche, based on the UV recorded upon pUS.